DESIGN AND ANALYSIS OF SUSTAINABLE URBAN DRAINAGE SYSTEM USING EPA-SWMM: A CASE STUDY OF UTP ACADEMIC COMPLEX - Bahari, Muhammad Rahimi (Universiti Teknologi PETRONAS, 2021)
Urbanization contribute towards more land surfaces converted into impervious surfaces and it subsequently reduce the soil infiltration capacity.